Evaluasi Penerapan SAK ETAP Atas Persediaan (Studi Kasus Pada PT. WKPI) - kristayani, ni luh putu; sri harta mimba, ni putu (E-Jurnal Akuntansi, 2014)
Inventories are essential for manufacturing companies. Inventory requires management, record keeping, and proper inventory valuation, so the company can provide useful information for the evaluation and internal control. The purpose of this study is to evaluate the suitability of SAK ETAP implementation of the inventory on SMEs which in this case is a manufacturing company. This research was conducted at the manufacturing company belonging to the medium  scale enterprises, namely Wisnu Karya Putra International Ltd. (WKPI Ltd.) in the city of Denpasar. Data used in this study is qualitative and quantitative data. The data source of this research is secondary data. The data collection was done by using documentation. The data analysis technique used is the analysis of qualitative data. Based on the evaluation found that the accounting for inventories at WKPI Ltd. has been in accordance with SAK ETAP applicable in Indonesia.
Keywords: inventory, PT. WKPI, SAK ETAP, SMEs